Clinico‐biological characteristics and treatment of type I monoclonal cryoglobulinaemia: a study of 64 cases. (2nd November 2014) - Harel, Stephanie; Mohr, Melanie; Jahn, Isabelle; Aucouturier, Francoise; Galicier, Lionel; Asli, Bouchra; Malphettes, Marion; Szalat, Raphael; Brouet, Jean‐Claude; Lipsker, Dan; Fermand, Jean‐Paul
Summary This retrospective analysis was conducted in 64 patients diagnosed with type I cryoglobulinaemia (CG) followed at two French centres. Median follow‐up was 6·75 years. CG was IgG in 60% and IgM in 40% of all cases and was asymptomatic in 16 patients (25%). Cold‐triggered ischaemic skin manifestations were observed in 33 patients (51%). Neurological manifestations were observed in 15 patients and renal manifestations in 13. Most of the patients with necrotic purpura (14/16, P = 0·009) and renal manifestations (11/13, P = 0·057) had IgG CG. IgG CG was associated with monoclonal gammopathy of undetermined significance (MGUS), myeloma, chronic lymphocytic leukaemia and lymphoplasmocytic lymphoma in 18, 13, 5 and 2 patients, respectively. IgM CG was associated with MGUS and Waldenström macroglobulinaemia in 8 and 18 cases, respectively. One third of patients did not receive any specific treatment. Various treatments, including rituximab, were administered to 25/31 patients with IgG CG and 6/25 patients with IgM CG due to CG‐related symptoms. Rituximab was ineffective in all cases associated with a predominantly plasmacytic proliferation. To conclude, type I CG has specific clinico‐biological characteristics compared to type II CG. Furthermore, there are differences in terms of related manifestations between type I IgG and type I IgM CG.